Aspects of Improvement in Exploitation Process of Passenger Means of Transport - Marian Brzeziński; Magdalena Kijek; Paulina Owczarek; Katarzyna Głodowska; Jarosław Zelkowski; Piotr Bartosiak (Journal of Advanced Transportation)
Effective exploitation of means of transport in transport companies is one of the most important ways of achieving competitive advantage. Mentioned problem is particularly important in the market of passenger transport services in large agglomerations, because it has a social aspect in addition to the economic dimension. In addition, most often the studies concern single objects of exploitation, while the subject of research are groups of objects of passenger transport means. The main objective of the study is to analyze and evaluate the system of exploitation of passenger transport means and to propose solutions for its improvement. On the basis of the theory of exploitation systems, quantitative utilitarian models have been built, which have been verified by applications using data obtained from Municipal Communication Company (MPK) in Wroclaw. Originality and innovation in the recognition of the research problem consist in applying to the analysis and evaluation of the Ishikawa diagram exploitation system, Pareto-Lorenzo analysis, and FMEA (Failure Mode and Effects Analysis) methods. On the other hand, a QFD (Quality Function Deployment) diagram was used to build a model of improvement of the exploitation system, with the use of which the target values of parameters for the operation of MPK passenger transport in Wroclaw were determined. The applied methods, techniques, and research tools are rarely used in the field of testing of vehicle operation systems. The work has a very practical character and built models can be used in other urban agglomerations in order to improve the operation of passenger transport means.